Digital Literacy for Teachers for Efficient Management of Learning Administration at MTS Al-Washliyah Kuala Silo Bestari Tanjung Balai - Daulay, Nurul Anjani; Daulay, Nurika Khalila (SAINTIS Publishing, 2025)
This study aims to determine the development of teachers towards digital. In the rapidly developing digital era, teachers' ability to utilize information and communication technology (ICT) is crucial not only in the learning process, but also in managing administrative tasks. This study uses a qualitative method with a case study approach on a number of teachers at MTs Al Washliyah Kuala Silo Bestari TanjungBalai. Data were collected through in-depth interviews and observations of the practice of managing learning administration carried out by teachers. The results of the study show that teachers with a high level of digital literacy tend to be more effective and efficient in completing administrative tasks such as preparing learning plans, managing student grades, making reports, and communicating with related parties. The use of various digital applications and platforms can reduce manual workloads, minimize errors, and speed up workflows. The implication of this study is the importance of improving teachers' digital literacy competencies through ongoing training and mentoring to optimize learning administration management and ultimately improve the overall quality of education. The use of various productivity applications, learning management systems (LMS), and digital communication tools has been shown to reduce dependence on manual methods that are prone to errors and time-consuming. The implications of this study emphasize the urgency of strengthening teachers' digital literacy through ongoing training programs, adequate technical support, and provision of relevant digital resources.